A New Caruncle-bearing Limnonectes (Anura: Dicroglossidae) from the Phu Phan Mountain Range in Northeastern Thailand - Rujirawan, Attapol; Yodthong, Siriporn; Wanchai, Pratyaporn; Stuart, Bryan; Aowphol, Anchalee (Tropical Natural History, 2025)
We describe a new species of dicroglossid frog in the genus Limnonectes from the Phu Phan Mountain Range, Sakon Nakhon Province, northeastern Thailand. Molecular phylogenetic analyses, based on the mitochondrial 16S ribosomal RNA gene, revealed that Limnonectes sirindhornae Rujirawan, Yodthong & Aowphol, sp. nov. is closely related to L. lauhachindai but has mean uncorrected pairwise genetic divergences of 4.25%. The new species can be distinguished from its congeners by having the combination of SVL 36.7–44.7 mm (n = 8) in adult males, 40.2–45.6 mm (n = 8) in adult females; adult males with hypertrophied heads; adult males with interorbital caruncle weakly developed, low-profiled, U-shaped, without free posterior margin; two enlarged odontoid processes on anterior margin of lower jaw, larger in males than in females; vocal sac opening in males absent; and yellowish coloration in life on ventral surfaces absent.